Ca2+ Signaling: Stimulation of Local Cytosolic Calcium Release by Photothermal Heating for Studying Intra‐ and Intercellular Calcium Waves (Adv. Mater. 24/2021). Issue 24 (18th June 2021) - Zhu, Dingcheng; Feng, Lili; Feliu, Neus; Guse, Andreas H.; Parak, Wolfgang J.
Abstract : Near‐infrared light excitation of individual polymeric capsules with integrated plasmonic nanoparticles enables release of Ca 2+ . The small amount of released Ca 2+ from lysosomes rapidly triggers robust Ca 2+ release from the endoplasmic reticulum, leading to a propagating intra‐ and intercellular calcium waves, as described by Wolfgang J. Parak and co‐workers in article number 2008261 .